Rapid and effective detection of Macrobrachium rosenbergii nodavirus using a combination of nucleic acid sequence-based amplification test and immunochromatographic strip - Lin, Feng; Shen, Jinyu; Liu, Yuelin; Huang, Aixia; Zhang, Haiqi; Chen, Fan; Zhou, Dongren; Zhou, Yang; Hao, Guijie (Journal of invertebrate pathology, 2023)
[Display omitted] •The NASBA-LFD for detecting MrNV-chin was developed by amlification at 41 °C in a single tube within 90 min followed by hybridization.•The NASBA-LFD was specific for MrNV.•Sensitivity of NASBA-LFD was about 104 times higher in comparison to PCR-based detection.•The NASBA-LFD would be a simple, rapid and reliable method for detection of WTD. Nucleic acid sequence-based amplification (NASBA) provides a fast and convenient approach for nucleic acid amplification under isothermal conditions, and its combination with an immunoassay-based lateral flow dipstick (LFD) could produce a higher detection efficiency for M. rosenbergii nodavirus isolated from China (MrNV-chin). In this study, two specific primers and a labelled probe of the capsid protein gene of MrNV-chin were constructed. The process of this assay mainly included a single-step amplification at a temperature of 41 ℃ for 90 min, and hybridization with an FITC-labeled probe for 5 min, with the hybridization been required for visual identification during LFD assay. The test results indicated that, the NASBA-LFD assay showed sensitivity for 1.0 fg M. rosenbergii total RNA with MrNV-chin infection, which was 104 times that of the present RT-PCR approach for the detection of MrNV. In addition, no products were created for shrimps with infection of other kinds of either DNA or RNA virus, which indicated that the NASBA-LFD was specific for MrNV. Therefore, the combination of NASBA and LFD is a new alternative detection method for MrNV which is rapid, accurate, sensitive and specific without expensive equipment and specialised personnel. Early detection of this infectious disease among aquatic organisms will help implement efficient therapeutic strategy to prevent its spread, enhance animal health and limit loss of aquatic breeds in the event of an outbreak.